Rewrite the equation as <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>9</mn></mrow></mfrac><mo>⋅</mo><mrow><mo>(</mo><mi>f</mi><mo>-</mo><mn>32</mn><mo>)</mo></mrow><mo>=</mo><mi>c</mi></mstyle></math> .

Multiply both sides of the equation by <math><mstyle displaystyle="true"><mfrac><mrow><mn>9</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> .

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>9</mn></mrow><mrow><mn>5</mn></mrow></mfrac><mo>⋅</mo><mfrac><mrow><mn>5</mn></mrow><mrow><mn>9</mn></mrow></mfrac><mo>⋅</mo><mrow><mo>(</mo><mi>f</mi><mo>-</mo><mn>32</mn><mo>)</mo></mrow></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Multiply <math><mstyle displaystyle="true"><mi>f</mi><mo>-</mo><mn>32</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mfrac><mrow><mn>9</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mi>c</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>32</mn></mstyle></math> to both sides of the equation.

Do you know how to Solve for f c=5/9*(f-32)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.